COMPARISON OF EAR DAMAGE CAUSED BY CATERPILLAR PESTS IN TRANSGENIC (BT) MAIZE HYBRIDS AND CONVENTIONAL MAIZE HYBRIDS - MICHELOTTO, MARCOS DONISETI; CARREGA, WILLIANS CÉSAR; DUARTE, AILDSON PEREIRA; FREITAS, ROGÉRIO SOARES DE (International Journal of Maize & Sorghum, 2020)
The use of transgenic (Bt) maize hybrids has been an important tool to minimize ear damages caused by the caterpillar pests Helicoverpa zea and Spodoptera frugiperda (Lepidoptera: Noctuidae). The objective of this work was to evaluate ear damages caused by caterpillar pests in maize hybrids with Bt technologies and in their respective conventional versions (non-Bt) for control of caterpillar pests that attack maize ears in the state of São Paulo, Brazil. Experiments were carried out in four regions of the state, in two summer crops (2009/10 and 2010/11), using a randomized block design with 6x2 factorial arrangements. The first factor was the hybrids and the second factor was the use or not of Bt technology. During harvesting, the percentage of damaged ears was evaluated and damage scores were attributed to a sample of 20 ears per plot. It was found that: (i) YieldGard and Total Liberty (both Cry 1Ab), Herculex (Cry 1F), VTPRO (Cry 1A.105 + Cry2Ab2) and Viptera (VIP3Aa20) technologies, regardless of the hybrid and the season crop, significantly reduce the ear damages and the percentage of damaged ears; (ii) hybrids expressing the Cry 1Ab protein are more damaged by caterpillar pests compared with other technologies; and (iii) there is great variability among hybrids when expressing toxins, even among those hybrids with the same Bt event.